The MacBlue binary transgene (csf1r-gal4VP16/UAS-ECFP) provides a novel marker for visualisation of subsets of monocytes, macrophages and dendritic cells and responsiveness to CSF1 administration. - Kristin A Sauter; Clare Pridans; Anuj Sehgal; Calum C Bain; Charlotte Scott; Lindsey Moffat; Rocío Rojo; Ben M Stutchfield; Claire L Davies; David S Donaldson; Kathleen Renault; Barry W McColl; et al. (PLoS ONE)
The MacBlue transgenic mouse uses the Csf1r promoter and first intron to drive expression of gal4-VP16, which in turn drives a cointegrated gal4-responsive UAS-ECFP cassette. The Csf1r promoter region used contains a deletion of a 150 bp conserved region covering trophoblast and osteoclast-specific transcription start sites. In this study, we examined expression of the transgene in embryos and adult mice. In embryos, ECFP was expressed in the large majority of macrophages derived from the yolk sac, and as the liver became a major site of monocytopoiesis. In adults, ECFP was detected at high levels in both Ly6C+ and Ly6C- monocytes and distinguished them from Ly6C+, F4/80+, CSF1R+ immature myeloid cells in peripheral blood. ECFP was also detected in the large majority of microglia and Langerhans cells. However, expression was lost from the majority of tissue macrophages, including Kupffer cells in the liver and F4/80+ macrophages of the lung, kidney, spleen and intestine. The small numbers of positive cells isolated from the liver resembled blood monocytes. In the gut, ECFP+ cells were identified primarily as classical dendritic cells or blood monocytes in disaggregated cell preparations. Immunohistochemistry showed large numbers of ECFP+ cells in the Peyer's patch and isolated lymphoid follicles. The MacBlue transgene was used to investigate the effect of treatment with CSF1-Fc, a form of the growth factor with longer half-life and efficacy. CSF1-Fc massively expanded both the immature myeloid cell (ECFP-) and Ly6C+ monocyte populations, but had a smaller effect on Ly6C- monocytes. There were proportional increases in ECFP+ cells detected in lung and liver, consistent with monocyte infiltration, but no generation of ECFP+ Kupffer cells. In the gut, there was selective infiltration of large numbers of cells into the lamina propria and Peyer's patches. We discuss the use of the MacBlue transgene as a marker of monocyte/macrophage/dendritic cell differentiation.